2020
DOI: 10.1186/s40359-020-00436-y
|View full text |Cite
|
Sign up to set email alerts
|

Social trust predicts sleep disorder at 6 years after the Great East Japan earthquake: data from a prospective cohort study

Abstract: Background: The physical and psychological health impacts on victims of the Great East Japan Earthquake (GEJE) have lasted for a long time. Some cross-sectional studies have reported a relationship between social networks and/or social support and mental health among victims. Previous studies were cross-sectional observations at one time point after a disaster, it remains unclear whether the lack of social trust soon after the GEJE predicts long-term mental health outcomes among the victims. The objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Two years after the GEJE, social isolation measured using the Lubben Social Network Scale 6 was significantly associated with depressive symptoms evaluated using the Center for Epidemiological Studies-Depressive Scale [ 47 ]. Among survivors of the GEJE, those who considered community trust weak in 2011 had significantly higher Athens Insomnia Scale scores, a measure of sleep disturbance, for the entire period up to 2017 [ 48 ]. However, little is known about its association between insomnia and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Two years after the GEJE, social isolation measured using the Lubben Social Network Scale 6 was significantly associated with depressive symptoms evaluated using the Center for Epidemiological Studies-Depressive Scale [ 47 ]. Among survivors of the GEJE, those who considered community trust weak in 2011 had significantly higher Athens Insomnia Scale scores, a measure of sleep disturbance, for the entire period up to 2017 [ 48 ]. However, little is known about its association between insomnia and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, Sugawara and colleagues reported that having the perception that those in one's community were undependable months following a natural disaster was predictive of greater insomnia issues over the subsequent 6-year span (B ranges from "−0.007" to "−0.013" in different analytical models that have controlled for different relevant factors) (p. 5) [74]. Yet, like some of the evidence base associated with the other factors, the overall dearth of a healthy assortment of longitudinal findings (or even just enough relevant findings in general), with the exception of some initial data (e.g., [74]), has rendered it difficult to make any clear-cut conclusion.…”
Section: Less Closely Knit Communitiesmentioning
confidence: 96%
“…As an example, findings from Alhasan and colleagues' study have suggested that insomnia complaints were more pronounced among individuals residing in an area with little "neighborhood social cohesion" in contrast to their more closely knit counterparts (with a prevalence ratio of "1.26" after accounting for other relevant factors) (p. 7) [73]. In a similar vein, Sugawara and colleagues reported that having the perception that those in one's community were undependable months following a natural disaster was predictive of greater insomnia issues over the subsequent 6-year span (B ranges from "−0.007" to "−0.013" in different analytical models that have controlled for different relevant factors) (p. 5) [74]. Yet, like some of the evidence base associated with the other factors, the overall dearth of a healthy assortment of longitudinal findings (or even just enough relevant findings in general), with the exception of some initial data (e.g., [74]), has rendered it difficult to make any clear-cut conclusion.…”
Section: Less Closely Knit Communitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Although reports of neck pain after natural disasters are rare, the prevalence of neck pain was reported to be high after the GEJE, and deteriorated subjective economic conditions were associated with neck pain onset [18]. Furthermore, stressful conditions after the disaster increase sleep disturbance [19], which may also be associated with neck pain; however, the association between sleep disturbance and neck pain after natural disasters has not been reported. Clarifying the association between sleep disturbance and neck pain is important to develop strategies for the treatment of neck pain among people after natural disasters, which is also useful for the general population.…”
Section: Introductionmentioning
confidence: 99%